Memory decline in young stroke survivors during a 9-year follow-up: A cohort study - Laari, Siiri; Turunen, Katri; Kauranen, Tatu; Mustanoja, Satu; Lahti-Pulkkinen, Marius; Tatlisumak, Turgut; Poutiainen, Erja (Frontiers in Neurology, 2022)
Introduction: A decade after stroke, young stroke survivors continue to suffer from cognitive impairment. However, it is not known whether this long-term cognitive outcome is caused in part by further cognitive decline or solely by incomplete recovery from the acute effects of ischemic stroke. We studied changes in three cognitive domains over a 9-year follow-up period after first-ever and only ischemic stroke. Patients and methods: In this prospective, two-center cohort study, we recruited consecutive 18- to 65-year-old patients with acute stroke between 2007 and 2009, along with demographically matched stroke-free controls. We performed comprehensive neuropsychological assessments at 3 months, 2 years, and 9 years after stroke, and we also performed neurological examinations at the time of inclusion and at the 9-year follow-up. We assessed the associations among stroke, follow-up time and long-term cognitive outcomes using repeated-measures analysis of variance. Results: The subjects comprised 85 patients who had had their first-ever and only ischemic stroke (mean age 53 years at inclusion), along with 31 stroke-free demographic controls. We compared the cognitive changes in patients to those in controls over a 9-year follow-up. After initial recovery between 3 months and 2 years after stroke, patients showed a decline in memory between 2 and 9 years after stroke compared to controls within the same time interval (immediate recall p < 0.001; delayed recall p < 0.001; list learning p < 0.001). Other than memory, we found no difference in cognitive changes between poststroke patients and controls. Discussion: Our main finding was memory decline over a decade in young first-ever stroke patients with no further stroke or neurodegenerative disease. Our study extends the previous results of further memory decline in elderly stroke survivors to young stroke survivors. Conclusion: Young stroke survivors might be at risk of memory decline over the decade following the stroke.